DESAIN PROTOTIPE UNIT FILTRASI UNTUK PENGOLAHAN LIMBAH AIR WUDHU - Mar’atus Sholihah; Vivin Setiani; Ria Rismawati; Nora Amelia Novitrie; Sekarsari Wibowo; Nur Fajar Aprilia Sari (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to design and evaluate a simple prototype filtration unit for the treatment of ablution (wudhu) wastewater generated from religious facilities. Ablution water is categorized as domestic wastewater that is commonly discharged directly into the environment without prior treatment, although it still poses a potential risk of pollution. The developed prototype employs a multi-layer filter configuration consisting of palm fiber, zeolite, activated carbon, and sponge, with a total media height of 40 cm and an operational flow rate of 100 L/h. Based on design calculations, the system achieved a Hydraulic Loading Rate (HLR) of 0.4 m³/m²·h and an Empty Bed Contact Time (EBCT) of 60 minutes, indicating conservative hydraulic characteristics with a relatively long contact time. Performance testing showed that the filtration unit effectively reduced turbidity from 3 NTU to 1.2 NTU, achieving a removal efficiency of 88%, and increased the pH value from 5.6 to 7.0, thereby meeting the Class II water quality standard as regulated in Government Regulation No. 22 of 2021. These findings demonstrate that the designed filtration system is effective in improving the physical quality of ablution wastewater and has strong potential for application in public facilities such as mosques and educational institutions to support water conservation and sustainable wastewater management.